Ophiostomatoid fungi synergize attraction of the Eurasian spruce bark beetle, Ips typographus to its aggregation pheromone in field traps - Jirošová, Anna; Modlinger, Roman; Hradecký, Jaromír; Ramakrishnan, Rajarajan; Beránková, Kateřina; Kandasamy, Dineshkumar (Frontiers in Microbiology, 2022)
The Eurasian spruce bark beetle, Ips typographus is a destructive pest of the Norway spruce (Picea abies). Recent outbreaks in Europe have been attributed to global warming and anthropogenic impacts. Bark beetles are guided by multiple complex olfactory cues throughout their life cycle. Male-produced aggregation pheromones, comprising 2-methyl-3-buten-2-ol and cis-verbenol, have been identified as the most powerful signals that can attract the dispersing conspecifics. In addition to host trees, bark beetles interact with multiple organisms, including symbiotic ophiostomatoid fungi, which may promote beetle colonization success and their offspring development. Previously, in a short-distance laboratory assay, we demonstrated that the adult I. typographus is attracted to the volatile organic compounds (VOCs) produced by three symbiotic fungi: Grosmannia penicillata, Endoconidiophora polonica, and Leptographium europhioides. Furthermore, the abundant fusel alcohols and their acetates were found to be the most attractive odorants in the fungal VOC profile. In this study, using a long-distance field-trapping experiment, we analyzed the role of fungal VOCs in dispersing I. typographus. Two types of fungal dispensers were tested in combination with pheromones in traps: 1) live cultures of fungi grown on potato dextrose agar, and 2) dispensers containing synthetic fusel alcohols and their acetates in equal proportions. Subsequently, the composition of VOCs emitted from live fungal dispensers was analyzed. We found that the symbiotic fungi synergistically increased the attraction of beetles to pheromones in field traps and that the dose range of volatile fungal cues depended on the fungal species. While a low dose of E. polonica, when combined with pheromones synergistically increased trapping efficiency, a high dose of L. europhioides was required to achieve the same. The synthetic mix of fungal fusel alcohols and acetates improved the catch efficiency of pheromones only at a low tested dose. VOC analysis of fungal dispensers revealed that all the three fungi produced fusel alcohols and acetates but in variable composition and amounts. Collectively, the results of this study show that, in addition to pheromones, bark beetles might also use volatile cues from their symbiotic fungi to improve colonization and reproductive success in their breeding and feeding sites.